(untitled) (Swiss Medical Weekly, 2015)
Biotechnological advances now enable the design of fully human antibodies to target specific antigens in a growing number of diseases. Monoclonal antibodies (mAbs) differ from traditional small chemical molecules in several ways: (1) biological production ‒ they are grown in and extracted from cell cultures; (2) specificity ‒ they demonstrate high target specificity, with a low risk of drug-drug interactions; (3) administration ‒ they are delivered parenterally (intravenously or subcutaneously); (4) dosage interval ‒ their extended half-lives generally allow for spaced dosing (from weekly to monthly). In cardiology, fully human mAbs directed against proprotein convertase subtilisin / kexin type 9 (PCSK9) have shown to be effective in reducing low-density lipoprotein cholesterol (LDL-C) in phase II clinical trials among patients with familial hypercholesterolaemia (FH). PCSK9 inhibitors have just received approval for the treatment of FH and clinical atherosclerotic disease, and patients not at target under maximally tolerated statin therapy or intolerant to statins. Large-scale phase III trials are currently assessing the role of PCSK9 inhibitors in the secondary prevention setting for patients with acute coronary syndromes (ACS) and poorly controlled LDL-C under evidence-based therapies. Another area currently under investigation for fully human mAbs in secondary prevention is their potential ability to inhibit inflammatory pathways. In this context, canakinumab, a specific mAb inhibiting interleukin-1β (IL-1β), has already received approval for the treatment of systemic juvenile idiopathic arthritis. The canakinumab anti-inflammatory thrombosis outcomes trial (CANTOS) is an ongoing trial assessing whether inhibition of IL-1β could reduce the occurrence of cardiovascular adverse events in 17,200 patients with ACS and with defined persisting inflammation.